2020
DOI: 10.1093/gerona/glaa258
|View full text |Cite
|
Sign up to set email alerts
|

The Interconnections Between Somatic and Ovarian Aging in Murine Models

Abstract: The mammalian female is born with a limited ovarian reserve of primordial follicles. These primordial follicles are slowly activated throughout the reproductive lifecycle, thereby determining lifecycle length. Once primordial follicles are exhausted, women undergo menopause, which is associated with several metabolic perturbations and a higher mortality risk. Long before exhaustion of the reserve, females experience severe declines in fertility and health. As such, significant efforts have been made to unravel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 100 publications
0
7
0
Order By: Relevance
“…111,135 Although ovarian aging can promote the development of subclinical and then clinical myocardial and vascular disease, cardiovascular risk may also predispose to ovarian aging (eg, atherosclerosis involving microvasculature of the ovaries), 136 and age-related somatic mutations can affect both. 137,138 Notably, additional approaches to clarifying hormonerelated cardiovascular risk can involve examining the relative effects of sex-determining hormones in genderaffirming hormone therapy within transgender populations. Early data suggest that transgender females experience increased thromboembolic disease compared to cisgender women, whereas transgender males develop lipid profiles reflecting their gender rather than natal sex potentially without adverse cardiovascular risk.…”
Section: Hormonal Effects On Life Course Trajectoriesmentioning
confidence: 99%
See 1 more Smart Citation
“…111,135 Although ovarian aging can promote the development of subclinical and then clinical myocardial and vascular disease, cardiovascular risk may also predispose to ovarian aging (eg, atherosclerosis involving microvasculature of the ovaries), 136 and age-related somatic mutations can affect both. 137,138 Notably, additional approaches to clarifying hormonerelated cardiovascular risk can involve examining the relative effects of sex-determining hormones in genderaffirming hormone therapy within transgender populations. Early data suggest that transgender females experience increased thromboembolic disease compared to cisgender women, whereas transgender males develop lipid profiles reflecting their gender rather than natal sex potentially without adverse cardiovascular risk.…”
Section: Hormonal Effects On Life Course Trajectoriesmentioning
confidence: 99%
“…111,135 Although ovarian aging can promote the development of subclinical and then clinical myocardial and vascular disease, cardiovascular risk may also predispose to ovarian aging (eg, atherosclerosis involving microvasculature of the ovaries), 136 and age-related somatic mutations can affect both. 137,138…”
Section: Hormonal Effects On Life Course Trajectoriesmentioning
confidence: 99%
“…The results indicated that the slower rate of primordial follicle activation (increased ovarian reserve) in these animals is associated with reduced accumulation of DNA damage in the oocytes and reduced macrophage infiltration of the ovaries. These studies add to the evidence for association of reduced gonadal aging with slower somatic aging in these mutants [ 95 ], and identify likely mechanisms of this association.…”
Section: Novel Mechanisms Linking Growth Hormone and Agingmentioning
confidence: 80%
“…It is also noteworthy that TCs upregulate cell proliferation pathways (e.g. mTOR), which increase with aging 105 , but more importantly have been linked to the activation of primordial follicles 106 .…”
Section: Discussionmentioning
confidence: 99%